1994
DOI: 10.3354/meps111171
|View full text |Cite
|
Sign up to set email alerts
|

The northeastern Chukchi Sea: benthos-environmental interactions

Abstract: Benthic faunal abundance, diversity, and biomass were examined in the northeastern Chukchi Sea to determine factors influencing faunal distribution. Four taxon-abundance-based benthic station groups were identified by cluster analysis and ordination techniques. These groups are explained, using stepwise multiple discriminant analysis, by the gravel-sand-mud and water content of bottom sediments, and the organic carbon/nitrogen (OC/N) ratio. In contrast to previous benthic investigations in the northeastern Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 44 publications
8
49
0
Order By: Relevance
“…We believe that high dominance and thereby low α-diversity and high β-diversity are related to environmental stress, and partly, therefore, by the way in which this affects environmental heterogeneity. Feder et al (1994) came to similar conclusions. They also related offshore/inshore dissimilarities in diversity in the northeastern Chukchi Sea to regional differences in environmental stress.…”
Section: Between-habitat (␤) Diversitysupporting
confidence: 58%
“…We believe that high dominance and thereby low α-diversity and high β-diversity are related to environmental stress, and partly, therefore, by the way in which this affects environmental heterogeneity. Feder et al (1994) came to similar conclusions. They also related offshore/inshore dissimilarities in diversity in the northeastern Chukchi Sea to regional differences in environmental stress.…”
Section: Between-habitat (␤) Diversitysupporting
confidence: 58%
“…Chukchi Sea : Feder et al 1994; Canadian shelf areas: Thomson 1982, Stewart et al 1985. Although the total number of taxa (712) reported here at 87 stations include 505 species, they represent only ~35% of that observed in the whole Barents Sea area (Zenkevich 1963, Sirenko 1998, the Pechora Sea can be regarded as considerably species-rich.…”
Section: Diversity and Community Structurementioning
confidence: 67%
“…Kusnetsov 1970, Thomson 1982, Long & Lewis 1987, Grebmeier et al 1989, Feder et al 1994, Dahle et al 1998, Sejr et al 2000. In the Pechora Sea open-sea areas the environmental conditions are typically more stable than in the highly varying coastal areas, which are affected by seasonal variations in ice scouring, freshwater discharge and temperature.…”
Section: Effects Of Abiotic Factors and Sediment Typementioning
confidence: 99%
“…Some authors (e.g., Feder et al, 1994Feder et al, , 2007Renaud et al, 2007) have suggested that depth may be more important than specific water mass characteristics in generating broad-scale biomass patterns in both seas, perhaps due, in part, to influences on high-biomass epifaunal assemblages. Depth serves as a proxy for multiple covariates including increased decomposition of production with greater water depth, water mass and current changes, stratification, water temperature and salinity, and interactions with topography and water mass movements.…”
Section: Standing Stocks Of Marine Benthosmentioning
confidence: 99%
“…5, see also Feder et al, 1994;Grebmeier et al, 2006a). In the Chukchi, benthic macrofaunal survey data are predominately from the eastern areas, thus potentially creating a bias in our sampling of the benthos (Feder et al, 1994;Grebmeier, 2012;Grebmeier et al, 2006a).…”
Section: Standing Stocks Of Marine Benthosmentioning
confidence: 99%